2015
DOI: 10.1186/s13075-015-0564-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prednisone on type I interferon signature in rheumatoid arthritis: consequences for response prediction to rituximab

Abstract: IntroductionElevated type I interferon (IFN) response gene (IRG) expression has proven clinical relevance in predicting rituximab non-response in rheumatoid arthritis (RA). Interference between glucocorticoids (GCs) and type I IFN signaling has been demonstrated in vitro. Since GC use and dose are highly variable among patients before rituximab treatment, the aim of this study was to determine the effect of GC use on IRG expression in relation to rituximab response prediction in RA.MethodsIn two independent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
(40 reference statements)
3
38
0
1
Order By: Relevance
“…This was supported by a prospective analysis of 14 RA patients commenced on rituximab with further validation in 26 RA patients, with an AUC of 0.87 [51]. Furthermore, prednisolone treatment drives down type I interferon signatures and prediction of rituximab response was therefore highest in the prednisolone-negative group with an AUC of 0.97 [62]. These data suggest that those patients with a high baseline type I interferon signature respond well to anti-TNF and less well to rituximab, which may indicate differences in pathogenesis in the two groups.…”
Section: Interferon Gene Signaturesmentioning
confidence: 74%
“…This was supported by a prospective analysis of 14 RA patients commenced on rituximab with further validation in 26 RA patients, with an AUC of 0.87 [51]. Furthermore, prednisolone treatment drives down type I interferon signatures and prediction of rituximab response was therefore highest in the prednisolone-negative group with an AUC of 0.97 [62]. These data suggest that those patients with a high baseline type I interferon signature respond well to anti-TNF and less well to rituximab, which may indicate differences in pathogenesis in the two groups.…”
Section: Interferon Gene Signaturesmentioning
confidence: 74%
“…As previously described, suppression of the IFN score by certain treatment could affect the applicability of the IFN signature as a biomarker for therapy response, particularly to rituximab [5, 19]. That is, the treatment-related suppression of IFN score might impair the discriminative capacity of the biomarker, which would consequently lead to more false predictions.…”
Section: Discussionmentioning
confidence: 99%
“…This work led to the development of a RTX response prediction model; more recent work by De Jong et al . has shown that because of glucocorticoid‐related suppression of the IFN‐score, the highest accuracy of rituximab response prediction is achieved in patients who are not treated with glucocorticoids .…”
Section: Biomarkers (The ‘Extended Phenotype’) and Treatmentmentioning
confidence: 99%
“…Moreover, Vosslamber et al showed that a good clinical response to rituximab is associated with a selective drug-induced increase in type I IFN-response activity [41]. This work led to the development of a RTX response prediction model; more recent work by De Jong et al has shown that because of glucocorticoid-related suppression of the IFN-score, the highest accuracy of rituximab response prediction is achieved in patients who are not treated with glucocorticoids [42,43].…”
Section: Biomarkers (The 'Extended Phenotype') and Treatmentmentioning
confidence: 99%